A review of design considerations for light-duty diesel combustion systems. (January 2016) - Miles, Paul C; Andersson, Öivind
Practical aspects of light-duty diesel combustion system design are reviewed, with an emphasis on design considerations reported by manufacturers and engine design consultancies. The factors driving the selection of compression ratio, stroke-to-bore ratio, and various aspects of combustion chamber geometry are examined, along with the trends observed in these parameters in recently released engines. The interactions among geometric characteristics, swirl ratio, and the fuel injection nozzle parameters are also reviewed.